A rhodium(I) dicarbonyl complex with a redox-active ferrocenyl phosphine-NHC ligand: Enhanced reactivity of the metal centre through ferrocene oxidation. (28th January 2015) - Debono, Nathalie; Daran, Jean-Claude; Poli, Rinaldo; Labande, Agnès
Graphical abstract: The behaviour of a new dicarbonyl rhodium(I) complex bearing an electroactive ferrocenyl phosphine-NHC ligand towards oxidation has been studied, proving that the electron density at the rhodium centre could be tuned by oxidation of the ferrocenyl group. This difference has been highlighted by infra-red spectroscopic measurements. Abstract: A rhodium(I) dicarbonyl complex bearing a bidentate ferrocenyl phosphine-NHC ligand has been synthesized and characterized by NMR, IR spectroscopy, mass spectrometry and X-ray diffraction methods. Its behaviour towards oxidation was investigated and revealed that changing the oxidation state of ferrocene can significantly modify the electron density at rhodium. Oxidation of the rhodium(I) dicarbonyl complex in acetonitrile furnished an air-stable rhodium(III) complex, stabilized by acetonitrile molecules and with an interesting C–H bond activation at ferrocene. This new rhodium(III) complex is active for the hydrosilylation of acetophenone and its derivatives.